A GREEN APPROACH FOR THE SYNTHESIS OF DRUG DELIVERY SYSTEM, MESOPOROUS SILICA GRAFTED ACRYLAMIDE –β- CYCLODEXTRIN COMPOSITE, FOR THE CONTROLLED RELEASE OF CURCUMIN - Mullassery, Manohar D; Fernandez, Noeline B; R, Surya; Thomas, Diana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The scope of the present study was the preparation and characterization of a novel composite acrylamide β-cyclodextrin grafted 3-aminopropyltriethoxysilane bentonite (AMCD-g-APSB), for the controlled delivery of curcumin (CUR). Methods: AMCD-g-APSB, was synthesized by solvent-free conditions using microwave irradiation. The structure and surface morphology of the composite was established using Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, thermal analysis, etc. Results: The swelling percentage of the composite depends on both time and pH of the medium. The maximum swelling of the composite occurred at a pH of 7.4. The maximum drug encapsulation was occurring at a pH 3. About 96.5% of drug was loaded at pH 3. In vitro biocompatibility study was performed, and the result showed good biocompatibility of the composite in the concentration range 2.5–50 μg/ml. Conclusions: Drug delivery study of the composite proved that CUR could be successfully released in a controlled manner in the colon without much loses of the drug in the stomach.